Research Colloquium - Ahmad, Ibrahim; Mohd Firdaus, Mohd Kamaruzaman (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
9 August 2012. The second research colloquium was held at the Mini Theatre, Block X. To honour the winning research teams at this year’s research exhibitions, CITREX and ITEX, Dr Fatmawati Latada and Abdul Kamil Jamaluddin were invited to present their research products.